Exploring the Phytochemical Diversity and Anti-Plasmodial Potential of Artemisia annua and Artemisia afra from Different Geographical Locations in Cameroon - Lahngong M. Shinyuy; Gisèle E. Loe; Olivia Jansen; Allison Ledoux; Benjamin Palmaerts; Lúcia Mamede; Naima Boussif; Olivier Bonnet; Bertin S. Enone; Sandra F. Noukimi; Abenwie S. Nchang; Kristiaan Demeyer; et al. (Molecules)
In Cameroon, like in other African countries, infusions of Artemisia afra and Artemisia annua are widely used for the management of health-related problems, including malaria. The secondary metabolite contents of medicinal plants vary between different geographical regions and seasons, directly influencing their effectiveness in treating ailments. This study explores the phytochemical diversity and anti-plasmodial potential of A. annua and A. afra from distinct geographical locations within Cameroon, aiming to define the optimal chemical composition in terms of anti-plasmodial activity. Extracts were prepared from plants collected from diverse regions in Cameroon during both the rainy and dry seasons, and their metabolic contents were analyzed using Thin-Layer Chromatography (TLC), High Performance Liquid Chromatography (HPLC), and Gas Chromatography (GC). Their anti-plasmodial potential was assessed on a chloroquine-sensitive 3D7 Plasmodium falciparum strain. Additionally, the environmental parameters of the collecting sites were retrieved from multispectral satellite imagery. The activity profiles of the samples were associated with their environment, with distinct phytochemical compositions observed for each sample based on its geographical origin and season. Traces of artemisinin were detected in some of the A. afra samples, but it was present in the A. annua samples at a significantly higher concentration, especially in the rainy season samples (highest concentration in the Adamawa region, at 8.9% m/m artemisinin in the dry extract). Both plants are active at different levels, with A. annua more active due to the presence of artemisinin and A. afra probably active due to the presence of polyphenols. Both season and geographical location influence both plants’ metabolic contents and hence their antimalaria activity. These findings suggest that the selection of a suitable Artemisia sample for use as a potential antimalarial treatment should take into consideration its geographical origin and the period of collection.